Sex-based differences in helmet performance in bicycle trauma. Issue 10 (7th April 2021) - Feler, Joshua; Maung, Adrian A; O'Connor, Rick; Davis, Kimberly A; Gerrard, Jason
Abstract : Objectives: To determine the existence of sex-based differences in the protective effects of helmets against common injuries in bicycle trauma. Methods: In a retrospective cohort study, we identified patients 18 years or older in the 2017 National Trauma Database presenting after bicycle crash. Sex-disaggregated and sex-combined multivariable logistic regression models were calculated for short-term outcomes that included age, involvement with motor vehicle collision, anticoagulant use, bleeding disorder and helmet use. The sex-combined model included an interaction term for sex and helmet use. The resulting exponentiated model parameter yields an adjusted OR ratio of the effects of helmet use for females compared with males. Results: In total, 18 604 patients of average age 48.1 were identified, and 18% were female. Helmet use was greater in females than males (48.0% vs 34.2%, p<0.001). Compared with helmeted males, helmeted females had greater rates of serious head injury (37.7% vs 29.9%, p<0.001) despite less injury overall. In sex-disaggregated models, helmet use reduced odds of intracranial haemorrhage and death in males (p<0.001) but not females. In sex-combined models, helmets conferred to females significantly less odds reduction for severe head injury (p=0.002), intracranial bleeding (p<0.001), skull fractures (p=0.001), cranial surgery (p=0.006) and death (p=0.017). There was no difference for cervical spine fracture. Conclusions: Bicycle helmets may offer less protection to females compared with males. The cause of this sex or gender-based difference is uncertain, but there may be intrinsic incompatibility between available helmets and female anatomy and/or sex disparity in helmet testing standards.